Comparación modelos de dispersión, CALPUFF y AERMOD (2017)
This paper analize the features of the dispersion models, Calpuff and Aermod in the way that the limitations and advantages are exposed. With de purpose of obtain a criteria of choice at the moment of deciding which model is best to a particular condition.